2003
DOI: 10.1007/s00425-003-1041-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient translocation in the xylem of poplar ? diurnal variations and spatial distribution along the shoot axis

Abstract: This investigation shows diurnal variations in the xylem sap composition of poplar (Populus tremula x P. alba). All major macronutrients reached a maximum concentration in the first half of the light period and decreased to the middle of the night. The relative abundance of the nutrients did not change during the day. The sap flow, which responded very fast to the environmental changes (2.2-fold increase within 10-20 min of illumination), reached a maximum value in the second half of the light period. Transpir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
78
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 45 publications
10
78
0
Order By: Relevance
“…The lowest IR was in xylem tissues in all cultivars. The nutrient content of xylem tissues is lower than that of other tissues (Siebrecht et al, 2003;Yadeta and Thomma, 2014), which explains why few endophytes colonize this tissue. Xylem possesses highly structured and rigid secondary xylem walls and pit membranes with extremely small pores.…”
Section: Tissue Preferencementioning
confidence: 99%
“…The lowest IR was in xylem tissues in all cultivars. The nutrient content of xylem tissues is lower than that of other tissues (Siebrecht et al, 2003;Yadeta and Thomma, 2014), which explains why few endophytes colonize this tissue. Xylem possesses highly structured and rigid secondary xylem walls and pit membranes with extremely small pores.…”
Section: Tissue Preferencementioning
confidence: 99%
“…The sole source of nitrogen for the leaf model was nitrate import from the xylem based on the observation that nitrate represents the main form of nitrogen (80%) entering a leaf (Macduff and Bakken, 2003). The rate of nitrate import into the leaf during the day:night was constrained to be 3:2 based on measurements in various plant species (Delhon et al, 1995;Macduff and Bakken, 2003;Siebrecht et al, 2003). Other than the export of Suc and amino acids, cellular maintenance costs were accounted for by including generic ATPase and NADPH oxidase steps for maintenance and the requirement to satisfy a specified carbon conversion efficiency (Cheung et al, 2013).…”
Section: A Day-night Modeling Framework For Leaf Metabolismmentioning
confidence: 99%
“…This diurnal pattern suggests that the xylem loading rate of nitrate is high in the light period but low in the dark period. Indeed, several studies have shown that root-to-shoot nitrate translocation rates are high in the day and low in the night (Macduff and Bakken, 2003;Siebrecht et al, 2003). Thus, in addition to the high transpiration rate, the high xylem loading rate in the light period could lead to the pronounced diurnal variation in the nitrate translocation rate.…”
mentioning
confidence: 99%